Financial Service and Performance of Chinese Private Companies: The Mediating Role of Technological Innovation - Wang, Xiaoran; Ibrahim, Haslindar; Bo, Le (Business Management and Strategy, 2024)
Financial performance is one of the key essential elements of financial management. Therefore, this research is to investigate the effects of financial service on the financial performance of private listed firms in China and looks at how firm technological innovation plays a mediating role in this relationship. This study includes 4,635 private listed companies in China from 2013 to 2022 and adopts a robust fixed effects model for benchmark regression. In the robustness test, two-stage least squares, alternative proxies and time segmentation are used to back up the findings. It is found that financial service is significantly and positively related to firm financial performance. Moreover, there is a potential mediating mechanism of corporate technological innovation along this path of the influence of financial service on firm financial performance. The findings provide empirical evidence for private firms and related groups such as policymakers in China.